MODEL PEMBELAJARAN TERPADU UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK DAN BERBICARA - Arianto Arianto (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This study aims to improve: (1) the teaching effectiveness of teachers, (2) students’ learning activities, and (3) listening and speaking skills of grade IX-2 students of SMP Negeri 17 Kendari through the application of integrated learning model. This research was conducted at class IX-2 of SMP Negeri 17 Kendari which consists of 32 students. This research is designed as descriptive study with classroom action research. The data collected in this study were analyzed descriptively, quantitatively and qualitatively. The results of this study indicate that the activities of teachers and students are increase; and the students’ learning outcomes of class IX-2 of SMP Negeri 17 Kendari through the application of integrated learning model are enhanced as well. The action took two cycles, in listening aspect with the speech messages as the lesson and speaking aspect with commenting on the content of the speech as the material. The improvement of learning outcomes for listening aspect is increased to 93.75%, and the speaking aspect to 87.5%.The results of this research are useful to increase the knowledge, give positive impact to improve learning result of Indonesian language at school, and increase knowledge about learning models and its application in learning process. Furthermore, the result can be a platform for further research development.